Manajemen Risiko Dalam Pengiriman Barang Pada Jasa JNT Express Cabang Palembang Ditinjau Dari Perspektif Ekonomi Islam - Yuliana Yuliana; Hilda Hilda; Fakhrina Fakhrina (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The main problem in this thesis is that in the last few months JNT Express Palembang branch has often experienced a decline in sales and also complaints from customers about the many problems that occur in the service felt by consumers such as problems with late delivery of goods, shipments that cannot be tracked, damage to goods to loss of delivery packages. These complaints were obtained from the Internet Media. The purpose of this discussion is to find out the Implementation of Risk Management in the Delivery of Goods at JNT Express Palembang Branch Services and Islamic Economic Review on Risk Management in the Delivery of JNT Express Palembang Branch Services. This research is a field research. By using qualitative methods. This research uses informants consisting of 6 people, namely 1 Leader, 1 Admin, 1 Courier and 3 JNT Palembang Branch Consumers. This research was conducted at JNT Ekpress, Jl. Sultan M. Mansyur, Bukit Lama, Kec. Ilir Barat I. Palembang City. While the data collection method in this study is in the form of observation, interviews, documentation. Based on the results of the study. Risks in shipping JNT goods are Social, Physical, Customer and Competition factors. The obstacles are delays, wrong addresses, damage and loss of goods. To prevent or minimize the occurrence of risks, JNT issues Standard Delivery Terms (SSP). Review of Islamic Economics on Risk Management in the Delivery of Goods Services JNT Express Palembang Branch is not contrary to Islam.